ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) DALAM UPAYA MEMINIMUMKAN BIAYA PRODUKSI PADA CV. DELAPAN-DELAPAN KUNINGAN - Maulana, Yopan; Rois, Tatang (Universitas Kuningan, 2018)
The research gap arises from the fluctuation of raw material inventory, the absence of safety stock and reorder point, and research gap from previous research that support EOQ (Economic Order Quantity) method and comparison with conventional method. The study aims to determine: (1) Whether the raw material inventory control method applied by CV. Delapan-Delapan is optimal, (2) Whether the method of EOQ (Economic Order Quantity) minimizes the production cost in CV. Delapan-Delapan, (3) how many optimal order of raw material at CV. Delapan-Delapan, (4) the amount of safety stock at CV. Delapan-Delapan, and (5) The time the CV. Delapan-Delapan do the Re Order Point if the company applies EOQ policy. The analytical method used in this research is descriptive analysis by comparing the total inventory (TIC) of EOQ calculation with total inventory cost (TIC) of conventional method. Data analysis techniques in this study uses Economic Order Quantity. The results shows that: (1) CV. Delapan-Delapan has not conducted optimal inventory control method to minimize the cost of economical inventory; (2) By applying EOQ method, the company can save total cost of raw materials of tapioca flour and wheat flour of Rp.17.553.366, - and Rp.11.109.966,- respectively; (3) Optimum raw material quantities for tapioca flour and wheat flour at CV. Delapan-Delapan are 1.441 kg and 1.177 kg, the amount of safety stock of tapioca flour and wheat flour is 1.026 kg and 703 kg, and (5) the company must do the re-order point when the quantity of raw material of raw tapioca flour and wheat flour in the warehouse has reached the amount of 1.199 kg and 811 kg respectively.Keywords: Total Cost Inventory, Re Order Point, Safety Stock, Economic Order Quantity